Sushi Domain Containing 2 (SUSD2) inhibits platelet activation and binding to high-grade serous ovarian carcinoma cells. (17th November 2018) - Lager, Tyson W.; Roetman, Jessica J.; Kunkel, Jacob; Thacker, Megan; Sheets, Jordan N.; Egland, Kristi A.; Miles, Cecelia M.; Larson, Mark K.; Gubbels, Jennifer A. A.
Abstract: Platelets play a central role in primary hemostasis affecting tumor survival and metastases. Tumors induce platelets to aggregate and bind to the cancer cells, resulting in protection from immune surveillance and often leading to thrombocytosis. In ovarian cancer (OvCa), one-third of patients present with thrombocytosis, a diagnosis that correlates with shorter survival. SUSD2 (SUShi Domain containing 2), a type I transmembrane protein, shown to inhibit metastatic processes in high-grade serous ovarian carcinoma (HGSOC), is expressed on endothelial cells and thus may influence platelet reactivity. As such, we hypothesized that SUSD2 levels in ovarian cancer-derived cell lines influence platelet activation. We incubated OvCa non-targeting (NT) and SUSD2 knockdown (KD) cell lines with labeled platelets and quantified platelet binding, as well as GPIIb/IIIa integrin activation. The role of GPIIb/IIIa in tumor cell/platelet interaction was also examined by measuring cell–cell adhesion in the presence of eptifibatide. We found that platelets exposed to OvCa cells with low SUSD2 expression display increased tumor cell-platelet binding along with an increase in GPIIb/IIIa receptor activation. As such, platelet activation and binding to HGSOC cells was inversely correlated with the presence of SUSD2. This represents one of the first tumor proteins known to provide differential platelet interaction based on protein status.